Molecular hydrogen-originated protonic acid site on Pt/WO3-ZrO2 - Triwahyono, Sugeng (Kolej Universiti Sains dan Teknologi Malaysia (KUSTEM), 2004)
Pt/WO3-ZrO2 catalyst exhibits high activity and selectivity in alkane skeletal isomerization which is important reaction for a gasoline of high quality. The catalytic activity and selectivity were enhanced in the presence of hydrogen. The roles of hydrogen present in the reaction mixture was studied by kinetic analysis of hydrogen adsorption nad IR study of the acid sites. The active sites on Pt/WO3-ZrO2 are interpreted in terms of a concept of acid site generation "molecular hydrogen-originated protonic acid site". The catalytic features of Pt/WO3-ZrO2 in comparison to those of Pt/SO4-ZrO2 are high selectivity for isomerization against cracking. The features arise from a fast surface diffusion of spiltover hydrogen atoms which convert into protons nad hydrides at Lewis acid sites. A high availablity of protons and hydrides causes high activity and selectivity for alkane isomerization.